Education, Human Capital and Competitiveness of Small Open Economies (Case of Georgia) - Mikiashvili, Nino (European Scientific Journal, ESJ, 2020)
Education policy, which must ensure the formation of human capital and sustainable economic growth of countries, is of a par+ticular importance for small open economies. The purposefulness of the education costs for the states having restored their independence not long ago is associated with certain risks. The goal of the work is to analyze the competitiveness of small developing economies in the context of expenditures borne for the formation of human capital. Improving a country’s competitiveness is always desirable, as it gives new opportunities to the society both, at personal and microeconomic and macroeconomic levels. In terms of modern technical and technological changes, small economies are unable to improve their competitiveness without permanent improvement of human capital. There is quite a close association between human capital quality and labor productivity, while labor productivity is influenced by the achievements in the field of education. The study accomplished within the scope of the present work considers such indicators as GPD per capita, education costs, net migration, average incomes, etc. The quantitative analysis is based on the use of regressive models. The causal factors were determined mainly by using the qualitative analysis. Traditionally, Georgia is a country prone to education what must have been an advantage of the country. The paper shows how much the country with a small economy could maintain qualified labor and ensure the economic growth, how much the country’s competitiveness and human capital changed. The gained results and experience must be interesting and useful for other small open economies.